The formation of a taste judgement: how Benjamin R. Haydon came to value, observe and evaluate the Elgin Marbles - Ardeta Gjikola; Marieke M.A. Hendriksen; Alexander Wragge-Morley (BJHS Themes, 2022)
What are taste judgements? Do they have a claim to knowledge? This article addresses these questions by revisiting the long-eighteenth-century debate on taste judgements and examining the case of a judgement that was unusually explicit about its formation. The painter Benjamin R. Haydon (1786–1846) encountered the Parthenon sculptures in 1808, studied them for several years, and recorded how he came to pronounce them ‘the finest things on earth’. I describe the maturation of Haydon's judgement, presenting the process as revealing of the nature of taste judgements. I argue that taste judgements are a distinct form of knowledge that involve expertise in three experiential aspects: valuation (prizing an artwork), observation (discriminating referential features in an artwork), and evaluation (assigning a specific worth to an artwork). From a methodological standpoint, Haydon's judgement draws attention to individual resources for the stabilization of knowledge and invites reflection on the status of the case as a unit of analysis in the history of science.